2015
DOI: 10.3109/09638288.2015.1059496
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of studies investigating the care of stroke survivors in long-term care facilities

Abstract: The care of stroke survivors in LTC facilities is lacking in rehabilitation, stroke specific care and secondary stroke prevention. This needs to be addressed through conducting further research to build a strong body of evidence to influence change in the care of this vulnerable group of patients. Implications for Rehabilitation Care of stroke survivors in long-term care facilities Stroke survivors make up almost a quarter of residents in long-term care facilities. They suffer from functional impairments and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…The findings suggest that, in Ireland, nearly one in five nursing home residents have experienced stroke prior to admission. Given that the national and international estimates of the prevalence of stroke among nursing home residents include stroke cases both before and after nursing home admission, the estimate of 17% (95% CI = 14.3–20.2%; N = 111) found in this study appears to be consistent with that found in the international literature (18–25%) [ 20 , 21 , 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings suggest that, in Ireland, nearly one in five nursing home residents have experienced stroke prior to admission. Given that the national and international estimates of the prevalence of stroke among nursing home residents include stroke cases both before and after nursing home admission, the estimate of 17% (95% CI = 14.3–20.2%; N = 111) found in this study appears to be consistent with that found in the international literature (18–25%) [ 20 , 21 , 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, the strength of the effect of PSCI on nursing home placement has varied between studies [ 16 ]. The characteristics of stroke survivors admitted to nursing homes have been examined in a number of studies [ 17 , 18 , 19 , 20 , 21 ]. These studies found high levels of care needs amongst stroke survivors residing in nursing homes.…”
Section: Introductionmentioning
confidence: 99%
“…There are approximately 30 million stroke survivors globally, and they comprise approximately one-quarter of the residents in long-term care (LTC) facilities. The care for stroke survivors in LTC facilities is lacking in rehabilitation, stroke-specific care, and secondary stroke prevention [ 43 ]. Additionally, it is necessary to continue in follow-up examinations, which are essential for coordinating post-acute services and monitoring of the patient’s progress [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the main focus of poststroke care is the outcome improvement and prevention of secondary stroke reoccurence; this is conducted using various tests, such as regular NT-proBNP monitoring. [91][92][93] whereby levels greater than 255 pg mL -1 pose significantly higher risk with a sensitivity of 76% and specificity of 60% (44). Today, NT-proBNP level is routinely measured using various immunoassay techniques (94), especially enzyme-linked immunosorbent assay (ELISA) for heart failure diagnosis.…”
Section: Introductionmentioning
confidence: 99%